CT-based sarcopenia and outcomes in patients undergoing VATS anatomical resection for NSCLC. (1st June 2022) - Hasenauer, A; Hungerbühler, J; Perentes, J; Abdelnour, E; Koerfer, J; Forster, C; Krueger, T; Becce, F; Gonzalez, M
Abstract: Objective: Sarcopenia is defined by a progressive loss of skeletal muscle mass and strength, combined with muscle fatty infiltration. Lung cancer patients frequently suffer from sarcopenia which may be associated with poorer post-operative outcomes. The aim of this study is to evaluate whether preoperative CT-based sarcopenia was associated with postoperative outcomes and survival after VATS resections in patients with early-stage non-small cell lung cancer (NSCLC). Methods: We retrospectively reviewed all consecutive patients that underwent anatomical resection for NSCLC between 2012 and 2019. The skeletal muscle index (SMI) and muscle quality (SMRA and IMAT) were measured at the L3 vertebral level on preoperative CT or PET/CT scans. We used the following SMI cut-off values for sarcopenia: 52.4 cm2 /m2 for men and 38.5 cm2 /m2 for women. Results: In total, 401 patients (sex ratio F/M: 173/228, mean age: 67 +/- 9.3 years) underwent VATS lobectomies (n=304) and segmentectomies (n=97) for NSCLC. Overall morbidity and mortality were 42.4% and 0.2%, respectively. The median length of stay was 7 days (IQR: 4–10). Sarcopenia was identified in 92 patients (23%). Patients with sarcopenia were predominantly males (75% vs 25%, p<0.001) and had lower BMI (21.4 vs 26.5, p<0.001). Patients with sarcopenia presented significantly increased morbidity (53.2% vs 39.2%, p=0.017) and had longer lengths of stay (6 vs 8 days, p=0.032). However, only lower BMI and ASA score >2 remained associated with increased morbidity on multivariate analysis. The median overall survival was comparable between patients with sarcopenia and those without sarcopenia (41 vs. 46 months, p=0.240). Conclusion: Based on CT assessment alone, preoperative sarcopenia appeared to have little impact on postoperative clinical outcomes or overall survival in patients undergoing VATS pulmonary resection. Further studies should also consider muscle strength and physical performance, in addition to CT imaging, for preoperative risk assessment.